The Moderating Role of Social Identity and Grit in the Association Between Parental Control and School Adjustment in Chinese Middle School Students - Ma, Chunhua; Ma, Yongfeng; Lan, Xiaoyu (Frontiers in Psychology, 2020)
Although the proliferation of empirical research has documented the association between parental control and school adjustment, findings of this linkage are still inconclusive. Moreover, fewer efforts have been made to address this association in middle school students. Guided by an ecological framework, the current study aimed to integrate the conflicting findings into a coherent body of knowledge, paying particular attention to two research purposes: (a) to examine the association between parental control and three objective indicators of school adjustment (social competence, academic grades, and peer acceptance), and (b) to explore whether this association was moderated by individual characteristics of social identity and grit. A total of 120 Chinese middle school students (42.5% females) aged between 13 and 15 years old were recruited for this study, and research data was gathered from multiple sources. To be specific, students were asked to complete a set of self-report questionnaires concerning parental control, social identity, and grit. Meanwhile, school-related social competence was rated by head teachers; academic grades were obtained from school records; peer acceptance was assessed by sociometric nominations. The results from hierarchical regression analyses showed that parental control was negatively associated with academic grades. Moreover, when reporting higher levels of social identity, parental control was negatively related to social competence and peer acceptance for those students with lower levels of grit. Our findings suggest that parental control can dampen middle school students’ academic performance, and low levels of grit can magnify the detrimental effect of parental control on social competence and peer acceptance in middle school students who regard themselves as closely connected to social groups.